Revision of the systematic status of patagonian and pampean gray foxes (Canidae: Lycalopex griseus and Lycalopex gymnocercus) using 3 D Geometric Morphometrics - Prevosti, Francisco Juan (2013)
Argentinean "zorros de campo" are currently included in two species: Lycalopex griseus and L. gymnocercus. Lycalopex gymnocercus lives in northern Patagonia and in most of central and northern Argentina. Lycalopex griseus is smaller and lives in Patagonia and throughout western Argentina. A previous traditional morphometric study using cranio-dental measurements considered both forms to be the same species, showing clinal reduction in size from northeastern to northwestern Argentina. Here we tested the synonymy of these foxes and the existence of clinal variation using a large sample and geometric morphometric methods. Our results rejected the separation of these foxes in two different species and confirmed, based on cranium and mandible size and shape that they belong to the same species. Also, we show there is a clinal variation in size that has an allometric component in cranial and mandibular shape, which accounts for the differences between these foxes.